Coagulation Activation and Tissue Necrosis in Meningococcal Septic Shock: Severely Reduced Protein C Levels Predict a High Mortality - Fijnvandraat, Karin; Derkx, Bert; Peters, Marjolein; Bijlmer, Rob; Sturk, Augueste; Prins, Martin H; Deventer, Sander J H van; ten Cate, Jan Wouter (Thrombosis and Haemostasis, 1995)
In 35 consecutively admitted children (mean age: 4.3 years) with a clinical diagnosis of meningococcal septic shock (MSS), activation of the coagulation and fibrinolytic pathways was evaluated directly at admittance to the paediatric intensive care unit (ICU). The association of clinical signs and haemostatic abnormalities was assessed.All patients had signs of extensive activation of the coagulation system. The 28-day mortality was 26%. Protein C activity was strongly reduced, especially in non-survivors in whom it was significantly lower than in survivors (5% versus 23%; p <0.0001). There was a strong negative correlation between protein C activity and the mean size of the skin lesions (r = -0.71, p <0.001). These results suggest that an acquired protein C deficiency in MSS is related to the pathogenesis of purpura fulminans.Furthermore, no increase in C4b-binding protein (C4BP) and no decrease in the ratio free protein S/total protein S was observed, suggesting that a deficiency of free protein S as a result of increased C4BP does not play a pathogenetic role in meningococcal septic shock.